2020
DOI: 10.1590/1807-3107bor-2020.vol34.0114
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported dental treatment needs during the COVID-19 outbreak in Brazil: an infodemiological study

Abstract: The aim of the present infodemiological study was to evaluate whether the COVID-19 outbreak has influenced the volume of content related to the dental treatment needs of Brazilian Twitter users to summarize the trends, and to identify the perceptions of the treatment needed. We collected tweets related to dental care needs of individuals exposed to the COVID-19 outbreak scenario between March 23 to May 4, 2020 and of those not exposed to the COVID-19 pandemic (unexposed group) on the same reported days of 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
(28 reference statements)
1
13
0
Order By: Relevance
“…In this perspective, the suspension of elective dental procedures during the COVID-19 pandemic outbreak might result in the reduction of the transmission rate and consequently reduce the pressure on the health care system ( 11 , 29 ). Conversely, the suspension of elective dental procedures might facilitate the deterioration of the oral health of the population, leading to irreparable damages and consequently reducing the quality of life of these subjects ( 18 ). Oral health and inequalities are a recognized major problem in the world, and such conditions is generally linked with lower-income segments of the population ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this perspective, the suspension of elective dental procedures during the COVID-19 pandemic outbreak might result in the reduction of the transmission rate and consequently reduce the pressure on the health care system ( 11 , 29 ). Conversely, the suspension of elective dental procedures might facilitate the deterioration of the oral health of the population, leading to irreparable damages and consequently reducing the quality of life of these subjects ( 18 ). Oral health and inequalities are a recognized major problem in the world, and such conditions is generally linked with lower-income segments of the population ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the suspension of non-urgent elective procedures may be seen as a relevant side effect of the measures adopted to reduce COVID-19 contamination, since the reduction of such treatments might result in significant oral health deterioration. ( 18 ) Therefore, it is important to assess the impact of COVID-19 on the number and type of dental procedures provided by the Brazilian public health system (Sistema Unico de Saude–SUS). Thus, the objective of this study was to assess the number of dental procedures performed in the SUS during the first wave of COVID-19 in Brazil (1 st semester of 2020) and compare it with the same period of 2019 using the SUS dataset (DATASUS).…”
Section: Introductionmentioning
confidence: 99%
“…Toothache disrupts the mood, sleep, eating habits, and social functioning of the individual, negatively affects quality of life, and is a condition that needs to be treated [ 10 , 13 , 27 ]. A study that analyzed the dental treatment needs of Brazilian Twitter users between 23 and 2020 and 4 May 2020 found that the need for treatment due to dental pain was ranked first [ 28 ]. Moreover, in the study in which Zhuo-Ying Tao et al analyzed the nature and spread of oral health information on COVID-19 using the Weibo media application, it was reported that the main health problem requiring treatment was toothache [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This infoveillance study was developed to assess the activity of Twitter users in Saudi Arabia regarding dental treatment needs and advice during the COVID-19 pandemic in 2020 comparing it with the activity in the same period in 2019. This study was performed using similar methods to those used in previous studies which assessed the use of Twitter during the COVID-19 pandemic [ 2 , 9 , 10 ]. Since this research used publicly available data that did not involve human subjects; thus, it did not require an institutional review board approval from Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia.…”
Section: Methodsmentioning
confidence: 99%